Naval sector in South Korea and Spain: comparative analysis of the main competitiveness indicators, 1970-1990 - Manzanal Oliva, Adrián (Papeles de Europa, 2017)
The study of a set of competitiveness indicators, and more in depth of unit labor costs, has allowed us to differentiate the origin of divergences in terms of competitive capacity between Spain and South Korea in the shipbuilding industry. The continued increase in productivity and wages in South Korea contrasts with the stagnation of these two variables in the case of the Spanish naval sector. South Korea, which has developed its naval industry in an adverse period of crisis, chose for a development export-based strategy. The competitive differences between Spain and South Korea are the result of very different industrial policy strategies during the period between 1970 and 1990.